Corporate Governance in Malaysia issues and challenges - Zulkefli, Nina Nurasyekin; Quddus, S. M. Abdul (International Islamic University Malaysia, 2019)
This paper deals with the complex relationship between governance and the moral dependency on the crisis of modernity. This crisis is reflected in the problem of achieving governance for its objectives, both in the political and economic system. The problem of governance is based on Carl Schmitt's central domain concept: that contemporary life is governed by the economic domain that describes human behaviour as neutral to things and actions, hence absolving mankind of their actions and choices. Thus many scholars have striven to rethink the nature of responsibility and its limits. This problem lies in the fact that modernity creates its moral patterns according to the dominant models of governance. They therefore cannot cancel and abolish this issue by themselves, but do in fact all work in tandem to make the issues more elusive by circumnavigating them; which ultimately means they cannot find a solution to the problem. Governance itself has been transformed from a moral system of responsibility and transparency to just procedures that can adapt to it or overcome these constraints. Some scholars believe that the problem of corruption, for example, derive from the same moral disposition that dominate people's behaviour and therefore is rationalized as acceptable. The paper thus concludes that a rethinking of morality and its relationship of governance requires more than just a restructuring of a range of legal and administrative procedure. There is rather a need to think radically about the nature of the current moral problem and its latent implications for governance.